Salmonella Kentucky: Antimicrobial resistance and molecular analysis of clinical, animal and environment isolates, Morocco - Bouchra Karraouan; Nadia Ziyate; Abdelaziz Ed-dra; Nadia Amajoud; Rachid Boutaib; Abdellah Akil; Abdellah El Allaoui; Hicham El Ossmani; Khalid Zerouali; Naima Elmdaghri; Brahim Bouchrif (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links on the page to access the full text.